Development and optimization of a high‐throughput HPLC–MS/MS method for the simultaneous determination of naringenin and its valine carbamate prodrug in rat plasma. (15th April 2021) - Xu, Xiaolan; Shen, Lulu; Xu, Qiuchi; Bai, Xiaochen; He, Zhonggui; Zhang, Tianhong; Jiang, Qikun
Abstract: A valine carbamate prodrug of naringenin (NAR) called 4'V was synthesized to enhance its oral bioavailability because of low water solubility and poor membrane permeability of NAR. This study developed and fully validated a sensitive, rapid, and robust HPLC–MS/MS method for the simultaneous determination of NAR and 4'V in plasma. The analytes were treated using liquid–liquid extraction, separated on a Phenomenex Kinetex XB‐C18 column, and detected using a triple‐quadrupole tandem mass spectrometer equipped with an electrospray ionization interface. The analytes were eluted within only 4 min by gradient procedure. The excellent linear correlations were validated over the range of 4–400 ng/mL ( r  = 0.9990) for NAR and 2–2000 ng/mL ( r  = 0.9951) for 4'V, with lower limits of quantification of 4 and 2 ng/mL, respectively. For all quality control samples, the intra‐day and inter‐day precision and accuracy were within ±15%. The validated method was economical, high throughput, and reliable and was first successfully applied to a pharmacokinetic study of NAR and 4'V after oral administration to Sprague–Dawley rats. The results of the pharmacokinetic study demonstrated that the idea of amino acid carbamate prodrug is a promising strategy to improve the bioavailability of NAR.